505 Attitudes towards risk reducing early salpingectomy with delayed oophorectomy for ovarian cancer prevention: a cohort study. (4th December 2020) - Gaba, Faiza; Blyuss, Oleg; Legood, Rosa; Izatt, Louise; Tripathi, Vishakha; Ragupathy, Kalpana; Crawfordd, Robin; Gareth Evans, D; Menon, Usha; Manchanda, Ranjit
Abstract : Introduction/Background: With increasing evidence and acceptability of the central role of the fallopian-tube in the etiopathogeneisis of epithelial ovarian cancer (OC), risk-reducing-early-salpingectomy-and-delayed-oophorectomy (RRESDO) has been proposed as a two-stage surgical alternative to risk reducing salpingo-oophorectomy (RRSO). RRESDO offers some level of risk reduction to women who decline/wish to delay RRSO whilst conserving ovarian function and avoiding detrimental consequences of premature-menopause. However, prospective outcome data for RRESDO are lacking. The aim of this study was to determine RRESDO acceptability and effect of surgical prevention on menopausal sequelae/satisfaction/regret in women at increased OC risk. Methodology: UK Multicentre, cohort, study (IRSCTN:12310993). OC unaffected UK women ≥18years, at increased OC-risk, with/without previous RRSO, ascertained through specialist familial-cancer/genetic-clinics and BRCA support-groups. High-risk women completed a 39-item customised questionnaire developed through literature review, expert clinician and patient support groups' involvement. Baseline characteristics were described using descriptive statistics. Logistic/linear-regression models analysed impact of variables on RRESDO acceptability and health-outcomes. Main outcomes were RRESDO acceptability, barriers/facilitators, menopausal-sequelae, satisfaction/regret. Results: 346 of 683 participants underwent risk-reducing salpingo-oophorectomy (RRSO) and 337 did not. 69.1% (181/262) premenopausal women who had not undergone RRSO found it acceptable to participate in a research study offering RRESDO. Premenopausal women concerned about sexual-dysfunction were more likely (OR=2.9, 95%CI=1.2–7.7, p=0.025) to find RRESDO acceptable. Women experiencing sexual-dysfunction after premenopausal-RRSO were more likely to find RRESDO acceptable in retrospect (OR=5.3, 95%CI=1.2–27.5, p<0.031). 88.8%(143/161) premenopausal versus 95.2%(80/84) postmenopausal women who underwent RRSO respectively were satisfied with their decision. 9.4%(15/160) premenopausal and 1.2%(1/81) postmenopausal women who underwent RRSO regretted their decision. HRT-uptake in breast-cancer (BC) unaffected premenopausal individuals was 74.1% (80/108). ). HRT-use did not significantly affect satisfaction/regret levels but reduced symptoms of vaginal-dryness (OR=0.4, 95%CI=0.2–0.9, p=0.025). Conclusion: Data show high RRESDO acceptability particularly in women concerned about sexual-dysfunction. Although RRSO satisfaction remains high, regret rates are much higher for premenopausal women than postmenopausal women. HRT use following premenopausal RRSO does not increase satisfaction and reduces vaginal dryness. Disclosures: Funding: Rosetrees Trust. RM declares research funding from Barts Charity and Eve-Appeal outside this work, honorarium for advisory board membership from Astrazeneca/MSD, and from Israel National Institute for Health Policy Research, support from NHS Innovation Accelerator Fellowship. UM has a financial interest in Abcodia, Ltd., a company for academic and commercial development of biomarkers for screening and risk prediction. DGE declares honoraria for advisory board membership from Astrazeneca. The other authors declare no conflict of interest.